Hyperthermia Targeting the Tumor Microenvironment Facilitates Immune Checkpoint Inhibitors - Li, Zihui; Deng, Jie; Sun, Jianhai; Ma, Yanling (Frontiers in Immunology, 2020)
Immune checkpoint inhibitors(ICI) has ushered a new era of cancer therapy, but ICI is only effective in immunoreactive patients. Efficacy of ICI is closely related to tumor microenvironment. Fever for long time were thought to directed regulate the immune response and artificial “fever” from hyperthermia modulate the tumor immune microenvironment by providing danger signals with heat shock proteins as well as subsequent actived immune systems. Encouraging results has achieved in preclinical studies focused on potential synergetic effect by combining hyperthermia with ICIs. In this review, we summarized a cluster of immune related factors that are complementary for the enhancement of the ICI within tumor immune cycle, with highlight on the immungenicity and immunoreactivity in tumor microenvironment, and review recent preclinical data of the combination regimens involving hyperthermia and ICI, to demonstrate the combined efficacy, and illustrate possible approaches to further boost the effectiveness of this combination.